Hubungan Sibling Rivalry Dengan Perkembangan Kemandirian Pada Anak Prasekolah di TK Islam Sultan Agung 4 Semarang - Rizky Amanullah; Indra Tri Astuti; Kurnia Wijayanti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
.The process of independence in early childhood is crucial for their development, especially in Kindergarten (TK) environments. However, the phenomenon of sibling rivalry often affects this development. This study aims to examine the relationship between sibling rivalry and independence development in early childhood at TK Islam Sultan Agung 4 Semarang. This study employed a quantitative design with a cross-sectional approach, and a sample was taken using total sampling techniques involving 74 respondents. Instruments were used to measure sibling rivalry and independence development. Data analysis was performed through univariate and bivariate analysis with Somers' d test. The results showed that the majority of respondents were male (42 people) and most were 5 years old. In addition, 61 respondents experienced high levels of sibling rivalry, while 44 respondents showed low levels of independence. Bivariate testing produced a ρ-Value of 0.413, indicating no significant relationship between sibling rivalry and independence development, with an r-value of -0.119 indicating a very weak relationship. These findings indicate that other factors, such as limited sampling, parental upbringing patterns, socio-economic conditions, and environmental influences, may also influence the results. Therefore, further research with a larger sample and considering external factors is recommended to obtain more comprehensive results.